Edukasi Pencegahan Rupture Perineum Melalui Pijat Perineum Pada Ibu Hamil Di PMB Mesrida Simarmata, Am Keb Tahun 2022 - srininta; Mesrida Simarmata; Eka Purnamasari; Hernita Nababan (Pusat Riset dan Inovasi Nasional, 2024)
Background: Perineal rupture is a rupture that occurs as a result of the process of the head exiting the birth canal. It had to be stitched and there were scars. To prevent perineal rupture, education is carried out about perineal massage for pregnant women. Objective: So that pregnant women know how to do perineal massage and are able to independently and routinely do perineal massage. Method: Pre and Post Design One Group. By providing a questionnaire to measure pregnant women's knowledge about perineal massage before the education and measuring again after the education is carried out. The service participants were pregnant women aged 34-36 weeks at PMB Mesrida Simarmata, Am Keb September-November 2022. Results: Before the education was carried out, the level of knowledge of pregnant women was only 50% who knew perineal massage well and after the education was carried out those who knew perineal massage thoroughly good 83%. Conclusion: Community service has been carried out and there has been an increase in pregnant women's knowledge about perineal massage after education about massage. Suggestion: That health workers continue to provide education on perineal massage